EXPERIMENTAL DETERMINATION OF TEMPERATURES IN CHARACTERISTIC SECTIONS OF THE WORKING ZONE OF A CLOSED TWO-PHASE THERMOSYPHON - G. V. Kuznetsov; A. E. Nurpeiis (Известия высших учебных заведений: Проблемы энергетики)
In article, presents the results of experimental determination of temperature distributions in characteristic sections of the working zone of a closed two-phase thermosyphon. A thermosyphon made of copper with a constant cross-sectional area is used to study heat transfer. The height of the heat exchanger is 161 mm, the thickness of the side walls is 1.5 mm, the bottom wall is 2 mm, the internal diameter of the evaporative part and the vapor channel is 39 mm. Experimental results give dependences of the change in the characteristic temperatures on the heat flux supplied to the bottom cover of the thermosyphon and the filling ratio. An increase in the heat flow at the bottom cover of the thermosyphon leads to a decrease in the temperature drop along the vapor channel and a reduction in the time to reach the stationary mode of operation. Experiments show that even at high thermal loads (up to 11,2  kW/m2) the temperature drops over the height of the thermosyphon do not exceed 9 K.